The death of the internet - Jakobsson, Markus (Hoboken : John Wiley & Sons, 2012)
Fraud poses a significant threat to the Internet. 1.5% of all online advertisements attempt to spread malware. This lowers the willingness to view or handle advertisements, which will severely affect the structure of the web and its viability. It may also destabilize online commerce. In addition, the Internet is increasingly becoming a weapon for political targets by malicious organizations and governments. This book will examine these and related topics, such as smart phone based web security. This book describes the basic threats to the Internet (loss of trust, loss of advertising revenue, l.
4.3 Content-Sniffing XSS Attacks: XSS with Non-HTML Content4.3.1 Introduction; 4.3.2 Content-Sniffing XSS Attacks; 4.3.2.1 Content-sniffing; 4.3.2.2 A detailed view of content-sniffing XSS attacks; 4.3.2.3 Why do mismatches happen?; 4.3.2.4 Finding content-sniffing XSS attacks; 4.3.2.5 Example 1: Under the hood of the HotCRP attack; 4.3.2.6 Example 2: An attack on wikipedia; 4.3.3 Defenses; 4.3.3.1 Server-side defenses; 4.3.3.2 Secure content-sniffing; 4.3.3.3 Adoption; 4.3.4 Conclusion; 4.4 Our Internet Infrastructure at Risk; 4.4.1 Introduction; 4.4.2 The Political Structure.
4.4.3 The Domain.
Includes bibliographical references.
Print version record.
Keywords: Internet -- Security measures; Electronic commerce -- Security measures; Data protection; Computer crimes; Electrical engineering; Engineering; Computer science; COMPUTERS -- Internet -- Security; COMPUTERS -- Networking -- Security; COMPUTERS -- Security -- General; Computer crimes; Data protection; Electronic commerce -- Security measures; Internet -- Security measures; Electronic books